Neodymium oxide thin film gate oxide on silicon substrate / Hetherin Karuppiah - Hetherin , Karuppiah (2018)
Metallic neodymium (Nd) films were sputtered on silicon substrates. The films then underwent thermal oxidation andthermal oxynitridation at various durations of 5 min, 10 min, 15 min, and 20 min. The optimized time was utilized to carry out thermal oxidation and thermal oxynitridation at various temperatures of 500°C, 700°C, 900°C, and 1100°C.Thermal oxidation in oxygen (O2) ambient produced neodymium oxide (Nd2O3) and thermal oxynitridation in nitrous oxide (N2O) ambient producednitrogen-incorporated neodymium oxide (NdxOyNz). Both thermal oxidation and thermal oxynitridationproducedfilms with compositions of cubic neodymium oxide (c-Nd2O3), orthorhombic neodymium silicate (o-Nd2Si2O7), monoclinic (m)-, tetragonal (t)-, and hexagonal (h)-silicon dioxide (SiO2). These compositions and phases were identified through X-ray diffraction (XRD). The existence of semicrystalline interface layer was further supported by Fourier transform infrared (FTIR) analysis, Raman analysis, energy dispersive X-ray (EDX) spectroscopy analysis, and X-ray photoelectron spectroscopy (XPS) analysis. As for thermal oxynitridation, nitrogen (N) element was detected through XPS analysis. A physical model describing theformation of Nd2O3 and NdxOyNz together withsemicrystalline interface layer is proposed and explained. In the study of the effects of thermal oxidationdurationat a fixed temperature of 700°C, 15-min sampleproducedthebest electrical properties through the measurement and analysis of current-voltage (I-V) and capacitance-voltage (C-V) characteristics. This sample also demonstrated single interfacial layer with inclusion of Nd2Si2O7 and SiO2.Scratch test is conducted in order to characterize the mechanical adhesion strength of the samples, in which, this testrevealed that the samples have scratch resistance up to 700N. By using the optimized thermal oxidation time of 15 min to study the effects of temperature, it was found that 900°C sample produced thebest I-V and C-V characteristics. The optimized thermal oxidation parameter,that is900°C for 15 min, yieldedthebest electrical properties withthehighestelectrical breakdown field of 5.26 MV/cm at thelowestleakage value of 2.02 x 10-6 A/cm2, thehighest barrier height (ØB) of2.91eV, thelowest effective oxide charge (Qeff) of 4.03 x 1024 cm-2, and thelowest average interface trap density (Dit) of ~ 1031 eV-1 cm-2with effective dielectric constant value of 7.03. Similar trend was observed for the formation of NdxOyNz, whereby the optimized thermal oxynitridation parameters of 900°C for 15 min,exhibited the best electrical properties of with highest electrical breakdown fieldof 5.27 MV/cm, thelowest leakage current of 9.96 x 10-6 A/cm2, thehighest ØBof 2.94eV, thelowest Qeff of 6.59 x 1024 cm-2, and thelowest Dit of ~ 1030 eV-1 cm-2 with effective dielectric constant value of 8.42.By comparing both Nd2O3 and NdxOyNz, nitrogen content in the films has improved the electrical properties. Based on this study, it is highly possible for Nd2O3 and NdxOyNzto be applied as high dielectric constant gate oxide material in advanced metal-oxide-semiconductor (MOS)-based technology.